Дополнительные сведения о рукокрылых Украины - Татаринов, К.А. (Вестник зоологии, 1967)
The article deals with the data on the first findings of Rhinolophus hipposideros Bechstein, 1800 in Khmelnitsky region on the 21st of October, 1961 and on the 7th-8th of July, 1962 and with the terms of propagation of these small beasts. Myotis bechsteini was found during hibernation in catacombs of Stradch village, Lvov region, on the 12th of November, 1964. The data are presented on the greatest accumulation of propagating Myotis myotis in Mokraya cave of Lokitka village, Ivano-Frankovsk region and on their ringing. The localities are reported of findings of Nyctalus noctula in Rovno and Volyn regions and Vespertilio murinus in Ternopol region of the Ukrainian SSR.